(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
Forest resources are the second largest natural resource in Nepal after water and play a crucial role in the country’s economic development. It has a high degree of potential to accelerate economic growth by creating employment opportunities for a large number of people and generating government revenue significantly. In addition to this, it contributes significantly to soil fertility, climate regulation, and the preservation of biodiversity. Forests provide essential resources such as fuel, raw materials, and fodder, and offer recreational benefits. Despite their importance, Nepal faces challenges in sustainable forest management due to political instability, corruption, and heavy dependency on forests for livelihoods. This paper has adopted descriptive and analytical research design. Secondary sources of data have been used to carry out this study. Descriptive statistical tools have been used to interpret results. This paper highlights the need for policy reforms, community participation, and anti-corruption measures to ensure sustainable forest management. It concludes that without these measures, the potential of Nepal’s forest resources for economic growth cannot be fully realised.